Cardiac Tamponade Secondary to Esophagopericardial Fistula - Caitlin T. Perez-Stable, BA; Lauren T. Callaghan, BS; Christopher K. Wong, MD, MSc; Jorge M. Escobar, MD; Mahboob Alam, MD (Texas Heart Institute Journal)
Esophagopericardial fistulas are an extremely rare structural defect that may arise from malignant or iatrogenic etiologies. This article reports the case of a patient with cardiac tamponade secondary to hydropneumopericardium from esophagopericardial fistula. Given the high morbidity and mortality of this condition, this article describes challenges in diagnosis and clinical decision-making to improve early identification and interdisciplinary management.